Consciência fonológica e o gênero autobiografia: uma sequência didática em uma turma do 2° ano do ensino fundamental - Reis, Geruza de Araújo Barreto (2023)
The present dissertation is the result of a pedagogical intervention structured in the stages of the didactic sequence (DS) of Dolz, Noverraz and Schneuwly (2004), which was applied to 2nd year elementary school students from the Aruanda Local School, belonging to the municipality of João Pessoa /PB. Its general goal was to work the phonological awareness through texts of the literary sphere, in order to broaden their skills concerning the Alphabetic Writing System (SEA) and stimulate autonomy and linguistic mastery regarding their autobiographical productions. For this study, we relied mainly on the theoretical contributions of Soares (1998, 2021), Ferreiro and Teberosky (1999), Antunes (2005), Morais (2020), Scherer (2012), Bortoni-Ricardo (2004, 2005, 2006) Bakhtin (1992), Marcuschi (2002, 2008), Dolz, Noverraz and Schneuwly (2004), Klüger (2009) and Lejeune (2008), among other renowned theorists who are dedicated to these areas of knowledge, as well as the contributions of the National Common Curriculum Base, BNCC (BRASIL, 2018), the notebooks of the National Pact for Literacy at the Right Age, PNAIC (BRASIL, MEC/SEB, 2012, 2015), along with other nationally based documents. Regarding the methodology, it is both qualitative and quantitative, based on Bardin (2016), Bortoni Ricardo (2008), Prodanov, and Freitas (2013), and refers to an research-action that follows the assumptions of Thiollent (2008), being anchored in Applied Linguistics (AL), according to Menezes (2009). To collect data, we used the students' first written production. Regarding the quantitative aspects, we analyzed them from the perspective of the Psychogenesis of Written Language, and in relation to the qualitative aspects, we observed the structural organization and linguistic elements that are inherent to autobiographical written production, a teaching instrument that gave us the necessary support to elaborate and execute the SD modules, which were motivated by texts from the literary sphere and involved interdisciplinarity, resulting in a final production, which enabled comparative analyzes between the two productions (initial and final). In the quantitative analysis, we verified the writing levels of the 15 (fifteen) authorized participants, and in the qualitative analysis, we compared 9 (nine) productions, in which we were able to verify the advances made between the respective productions and understand the mistakes in the written records, due to the nuances of our language. Regarding the results of the present study, we emphasize that there were expressive and significant developments, both in terms of the development of SEA and also in the organizational structure of the autobiographical text, which proves the benefits of texts from the literary sphere for the development of phonological awareness and, consequently, the levels of writing, and, of DS, for the procedural teaching of written production of the textual genre autobiography.